Anatomical, physiological and transcriptional responses of two contrasting poplar genotypes to drought and re‐watering - Cao, Xu; Jia, Jingbo; Zhang, Chao; Li, Hong; Liu, Tongxian; Jiang, Xiangning; Polle, Andrea; Peng, Changhui; Luo, Zhi‐Bin (Physiologia Plantarum, 2014)
Populus × euramericana (Pe) displays higher stable carbon isotope composition ( δ 13 C ) and intrinsic water use efficiency ( WUE i ) than Populus cathayana (Pc) under unlimited water conditions, rendering us to hypothesize that Pe is better acclimated to water deficiency than Pc. To examine this hypothesis, saplings of Pc and Pe were exposed to drought and subsequently re‐watered. Pc and Pe exhibited distinct anatomical, physiological and transcriptional responses in acclimation to drought and re‐watering, mainly due to stronger responsiveness of transcriptional regulation of genes encoding plasma membrane intrinsic proteins ( PIPs ), higher starch accumulation, δ 13 C , stable nitrogen isotope composition ( δ 15 N ) and WUE i , and lower reactive oxygen species ( ROS ) accumulation and scavenging in Pe. In acclimation to drought, both poplar genotypes demonstrated altered anatomical properties, declined height growth, differential expression of PIP s, activation of ABA signaling pathway, decreased total soluble sugars and starch, increased δ 13 C, δ 15 N and WUE i , and shifted homeostasis of ROS production and scavenging, and these changes can be recovered upon re‐watering. These data indicate that Pe is more tolerant to drought than Pc, and that anatomical, physiological and transcriptional acclimation to drought and re‐watering is essential for poplars to survive and grow under projected dry climate scenarios in the future.

Phosphorus and nitrogen physiology of two contrasting poplar genotypes when exposed to phosphorus and/or nitrogen starvation - Gan, Honghao; Jiao, Yu; Jia, Jingbo; Wang, Xinli; Li, Hong; Shi, Wenguang; Peng, Changhui; Polle, Andrea; Luo, Zhi-Bin (Tree Physiology, 2016)